Unsettling decolonizing geographies. Issue 7 (25th June 2018) - de Leeuw, Sarah; Hunt, Sarah
Abstract: Geographers have long reflected on our discipline's colonial history. Both Indigenous and non‐Indigenous geographers have discussed ways of engaging Indigenous geographies and sought new ways of opening and expanding spaces for Indigenous peoples and Indigenous ways of knowing and being in our discipline. Like many social scientists, geographers name and frame this work in different ways; of late, decolonizing concepts and practices are increasingly deployed. As documented by especially Indigenous scholars, however, the discipline has yet to achieve much semblance of decolonization. This paper takes as a starting point that, despite good intentions, efforts at decolonizing geography are inherently limited because colonization continues to structure the field of geography and the academy more broadly. We begin by placing ourselves in conversations about Indigenous geographies and colonial violence, using this placement as a jumping off point for discussing ways geographers past and present approach decolonization. We pay particular attention to ways theories and articulations about decolonization may be falling short. Second, we offer a critical analysis of decolonization in relation to settler colonial power, including theories and praxes of engaging Indigeneity and Indigenous peoples and places. We discuss Indigenous geographies, what they mean, and to whom they have those meanings. We then turn to Indigenous knowledges and Indigenous ways of being and living in the world, problematizing how within more purely conceptual realms and often by non‐Indigenous peoples and geographers, these can be uncoupled or disconnected from ways decolonization is circulated and lived. We conclude with cautions and suggestions, based especially on provocations of Indigenous scholars, about ways geographers might unsettle our work in ongoing efforts toward decolonizing our discipline.